The impact of COVID-19 on stock market returns: Case of Bourse Regionale des Valeurs Mobilieres - Gnahe, Franck Edouard; Huang, Fei-Ming; Ashraf, Junaid (Technium Social Sciences Journal, 2021)
Using the pooled ordinary least square approach, this paper investigates the effect of Covid-19 on the regional financial exchange namely, Bourse Regionale des Valeur Mobileres (BRVM). In this note, we propose the hypothesis that COVID-19 has affected the regional financial exchange rate resistance to the shocks. We find that the regional financial exchange reacted proactively to the pandemic in the time of March 04, 2020 to April 20, 2020 after the occurrence. Our analysis also suggest negative regional market reaction was strong during the early days of the pandemic. However, this impact is transitory with implementation of official government policies, the stock returns maintain steady growth. We conclude that pandemic has changed the resistance of the regional financial exchange to shock. Therefore, the policy implications is to consider these asymmetries when determining the monetary policy and effectiveness of financial system rules to promote competitive emerging market structures and trade liberalization in the regional exchange market and developing countries.